Development of an intestinal epithelial cell line and organoids derived from the same swine and characterization of their antiviral responses - Matsumoto, Kaho (2024)
Intestinal homeostasis and integrity are important factors for maintaining host health. This study established intestinal epithelial cell lines and organoids from the same swine jejunal crypts to develop seamless swine intestinal in vitro evaluation systems. The study evaluated the proliferative capacity and tight junction formation of the epithelial cell line and characterized the cell differentiation potential of the intestinal organoids. The evaluation systems were subsequently exposed to the TLR3 agonist poly(I:C) to simulate viral infections and assess the antiviral responses. The results demonstrated no differences in the response to type I interferons. There were, however, significant differences in the expression of interferon-stimulated genes. This study collectively introduced a flexible evaluation system using cell lines and organoids and revealed notable differences in the expression of interferon-stimulated genes, highlighting the complexity of the immune responses in these in vitro systems and the importance of intestinal heterogeneity in assessing viral responses.